ADMINISTRASI TRADISIONAL SEBAGAI BASIS PEMBENTUKAN IDENTITAS KOLEKTIF PADA MASYARAKAT ADAT GEBONG MEMARONG DI BANGKA BELITUNG - Dewi Shinta; Waldimer Pasaribu; Irwan Irwan (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the role of traditional administration in shaping and maintaining the collective identity of the Gebong Memarong indigenous community in Bangka Regency. Amidst the challenges of modernization, previous studies have predominantly focused on agrarian conflicts and legal recognition, leaving a research gap regarding the role of traditional administration as a basis for identity reproduction. Employing a qualitative approach with ethnographic methods, data were collected through participant observation and in-depth interviews, then analyzed using the Miles and Huberman interactive model. The findings reveal that traditional administration is not merely a social regulation mechanism but a primary instrument for social integration through customary deliberation, leadership, and cultural rituals. From Talcott Parsons’ structural-functionalist perspective, traditional administration performs the integrated functions of Adaptation, Goal Attainment, Integration, and Latency (AGIL) to maintain community resilience. These findings emphasize that strengthening local institutions is key to negotiating cultural identity amidst modern bureaucratic pressures. Academically, this study enriches sociological discourse on the resilience of traditional institutions, while practically providing a foundation for indigenous protection policies through the recognition of local governance systems.